Hemoglobin Genotypes and their Relationship with Some of the Component of the Blood Parameter and Live Weight in Awasi/ sheep (Journal of Hama University, 2020)
The research was conducted on 46 sheep from the Awasi dynasty at a private farm in Hama. The hemoglobin, AA, AB, BB, hemoglobin, hematocrit, erythrocyte, and globular size, as well as the average blood hemoglobin concentration in the sheep blood corpuscles were determined to study their relationship with hemoglobin DNA structures using electrolyte gel on agarose gel. Results: There are statistical relations as follows:1 - The relationship of genetics of blood hemoglobin with the amount of hemoglobin in the red blood cell recorded the highest value of hemoglobin average blood samples studied at the genetic makeup AA and amounted to. 9.36 g / dl2 - the relationship of blood hemoglobin structures with hematocrit recorded the highest value of the average hematocrit in the structure of AA and amounted to 33.09%.3 - relationship of the genetics of blood hemoglobin with the erythrocyte count in sheep blood and the highest value in the genotype AA 9.12mil / mm3.4 - the relationship of the genomes of blood hemoglobin with the size of red corpuscle MCV reached 36.6fl in the genotype AA.• Relationship of blood hemoglobin structures with mean hemoglobin concentration in the red blood cell (MCHC) With 28.28g / dl in the AA genotype.6 - Relationship of the structure of blood hemoglobin with live weight: the highest value of 47.3Kg in the composition Hereditary AA, the lowest in the BB genotype was 44.2Kg.